EFFECTS OF COLONIC DISEASES ON CHILDREN’S HEALTH - Isaqova Nasiba Raxmatjonovna (Scholar Express Journals, 2023)
Physical development reflects the growth and developmental processes of the body at certain stages of ontogeny when genotypic data are phenotypically manifested under the influence of environmental factors. Accordingly, environmental factors affecting the physical development of children and adolescents require an individual and regional study of each organism's lifestyle, depending on the state of health. The data obtained are compared to certain parts of the body (head, neck, chest, abdomen and pelvis, arms and legs) and growth or change is observed. Anthropometric data are used not only in medicine but also in criminology to describe and identify criminals
Keywords: Anthropometric; length; width